Sustainable Bioethanol Production from Carica (Carica pubescens) Peel Waste: Optimization of Acid Hydrolysis and Fermentation Time - Sofana Ubaidilah; Akhmad Irfan; Sunaryo Sunaryo; Keodouangdy Yongthong; Rizky Mulya Sampurno; Berwyn Dzaky Radhitya (CV FOUNDAE, 2025)
The global energy crisis and continued reliance on fossil fuels have intensified the search for sustainable alternative energy sources, particularly biomass-derived biofuels. One promising yet underutilized resource is the peel waste of Carica pubescens, a papaya variety indigenous to the Dieng Plateau. This study investigates the potential of Carica peel waste as a bioethanol feedstock through sulfuric acid (H₂SO₄) hydrolysis and fermentation using Saccharomyces cerevisiae. To optimize sugar yield, the concentration of H₂SO₄ was varied between 0.1 M and 0.8 M, while fermentation durations were set at 96, 120, 144, and 168 hours. Results indicated that hydrolysis with 0.8 M H₂SO₄ produced the highest sugar concentration (6.8%). The most effective fermentation period was 120 hours, yielding 64% bioethanol with a density of 0.8679 g/mL, a calorific value of 4,831 kcal/kg, a flame height of 14.6 cm, and a combustion temperature of 438°C. These findings demonstrate the viability of Carica peel waste as a valuable raw material for bioethanol production. Its high efficiency and favorable fuel properties highlight its potential for integration into local renewable energy initiatives, contributing to sustainable energy development. Further studies on large-scale implementation and process optimization are recommended to maximize its industrial application.